Vitamin D receptor activation raises soluble thrombomodulin levels in chronic kidney disease patients: a double blind, randomized trial. Issue 5 (13th April 2018) - D'arrigo, Graziella; Pizzini, Patrizia; Cutrupi, Sebastiano; Tripepi, Rocco; Tripepi, Giovanni; Mallamaci, Francesca; Zoccali, Carmine
Abstract: Background: Thrombomodulin (TM) is a proteoglycan highly represented in the endothelial glycocalix that regulates the haemostasis and the endothelial response to inflammation. High soluble TM levels underlie a lower risk for coronary heart disease in population studies. Activation of vitamin D receptor (VDR) upregulates TM, but the effect of this intervention on soluble TM has never been tested in chronic kidney disease (CKD) patients. Methods: We performed a post hoc analysis of a 12 weeks double blind, randomized, placebo-controlled trial testing the effect of VDR activation by paricalcitol (PCT) on endothelium-dependent flow- mediated vasodilatation (FMD) in the forearm (ClinicalTrials.gov identifier: NCT01680198). Circulating TM was measured in the whole CKD population [88 patients: PCT n  = 44; placebo n  = 44] that took part into this trial. Results: Soluble TM at baseline was inversely related to the glomerular filtration rate ( r  = −0.65, P < 0.001) and to FMD (Spearman's ρ = −0.29, P = 0.01). Alongside the expected effects on bone mineral biomarkers, PCT produced a consistent rise (P = 0.005) in TM levels, from a median value of 8446.0 pg/mL [interquartile range (IQR): 6227.8–10 910.8 pg/mL] to 9127.5 pg/mL (6393.0–11 287.3 pg/mL) while placebo had no effect (between-groups difference P = 0.008). TM levels re-approached baseline values 2 weeks after stopping PCT. TM changes across the trial paralleled simultaneous changes in FMD. Conclusions: VDR activation by PCT raises TM levels and FMD and such effects are rapidly reversible after stopping the treatment. The TM rise induced by PCT is a possible mechanism whereby improvement in endothelial function by VDR activation may favourably impact upon vascular health in CKD patients.